DIAPHRAGMATIC MUSCLE STRENGTHENING THROUGH FUNCTIONAL ELECTRICAL STIMULATION (Fiep Bulletin - online, 2014)
The aim of this study was to analyze the final results to prove the effectiveness of the application of functional electrical stimulation on diaphragm in increased respiratory muscle strength in healthy patients. The study included 20 healthy subjects of both sexes, with male predominance of 70% and with an average age of 33.90 ± 12.37 years. Initial evaluation, application of 20 minutes FES and final evaluation: a single session for each individual, approximately 40 minutes, where it was held was held. Where spirometry, maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP) were assessed before and after each session. Statistical analysis of data was performed by the Kolmogorov-Smirnov test (p0.05). All study subjects were positive and satisfactory results can therefore conclude that the application of FES was effective in increasing of respiratory muscle strength.
Keywords: Electric Stimulation; Diaphragm; Muscular Strength.